Fungsi Partai Politik Dalam Pendidikan Politik Masyarakat - Khusnul Catur Prasetya; Zamroni Ishaq (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
One of the functions of political parties in legislation is as a means of political education and socialization. Political parties are obliged to disseminate their political discourse to the public. However, in its implementation in the field, there are still political parties that have not maximized their function in providing political education to the public. This study discusses (1) What is the function of political parties in providing public political education and its influence on public participation in general elections? (2) What are the implications of political parties that do not implement public political education? This research was conducted by using normative legal research methods, primary and secondary sources of legal materials, methods of collecting legal materials using statute records and others, and analyzing legal materials using descriptive analysis methods. The results of this study indicate that according to Law No.2 of 2011, one of the functions of political parties is to provide political education as a means of education for the wider community to become Indonesian citizens who are aware of their rights and obligations in public. The importance of political education carried out by political parties to the maximum and in its actual essence will be able to have a very good impact on society, which means that people are able to become people who are aware of their obligations in giving choices to political parties or candidates who are true and sincere in terms of welfare